A Differential Equation Based Model of Cell and Cytokine Activation Influenced by Glucose Dynamics and Elevated Cortisol Levels Due to Aging - Quintela, Bárbara M.; Marins, Thaís S.; Garan, Steven A.; Suen, Elliott K.; Talaei, Kian; Martins, Nuno R. B.; Jahansooz, Julia R.; Piszker, Walter (Anais do Simpósio Brasileiro de Computação Aplicada à Saúde (SBCAS), 2023)
Immunosenescence refers to the alterations in the immune system that occur due to the aging process, which increases susceptibility to diseases and reduces vaccine efficacy. Consequently, understanding the impact of aging on the immune system is crucial for simulating the different ways in which it can be challenged, thereby increasing life expectancy and quality of life. This study combines two mathematical models to understand how cortisol affects and is affected by the glucose uptake and the proand anti-inflammatory cytokines under infection. Cortisol concentration follows a diurnal rhythm and increases with glucose intake. The model simulates the influence of cortisol on the immune response, specifically through cytokine regulation.